TA’LIM SIFATINI OSHIRISHDA MOLIYALASHTIRISH TIZIMI SAMARADORLIGINI AHAMIYATINING TASHKILIY TUZILMASINI ISHLAB CHIQISHNING AHAMIYATI - Primkulova Zilola Abrorovna; Axmedjanov Karimjon Bakidjanovich (TADQIQOTLAR.UZ, 2024)
Annotatsiya:The education system is a very complex socio-economic system, which is characterized not only by quantitative, but also by qualitative characteristics, territorial distribution and administrative subordination.